SAT0100 Bone marrow OEDEMA is more associated with rapid radiographic progression than synovitis or bone erosion by using low field MRI in bio-naïve rheumatoid arthritis patients treated with adalimumab and methotrexate combination therapy. (23rd January 2014) - Katayama, K.; Okubo, T.; Sato, T.; Fukai, R.; Miyoshi, N.; Matsuno, T.
Abstract : Background: Rapid radiographic progression (RRP) has occurred in some rheumatoid arthritis (RA) patients regardless of any type of biological therapy. However, early diagnosis of RRP is still unknown. Objectives: The aim of this study is to find predictive MRI findings for RRP in RA patients. Methods: Twenty two RA patients, who treated for 1 year with Adalimumab (ADA) and methotrexate (MTX) combination therapy, were examined by radiography for both hands and feet using total Sharp-van der Heijde scoring (SHS) and compact MRI for both hands using cMRI score (cMRIS) (1) in low field MRI (0.3T) at baseline and 1 year after treatment. We analyzed to find the relationship between MRI and radiographic findings compared with RRP (SHS/y≥3) and non RRP (SHS/y <3) group. Results: Patients baseline demographics were: mean age: 60.1 year; RA disease duration: 8.4 year; baseline DAS28(ESR): 6.28; estimated ΔSHS/y: 13.7/y and HAQ-DI:1.9. At 1 year, 60.9% of patients achieved radiographic remission (ΔSHS/y <0.5) and ΔSHS/y was -0.5 (ΔJSN/y: 0.96, ΔJEN/y: -1.54). The cMRI showed 46.8%, 70.9%, 22.7% and 39.8% improvement of cMRIS synovitis, cMRIS oedema, cMRIS erosion and cMRIS erosion + synovitis + oedema, respectively. Three patients were assessed for RRP group (n=3, SHS=6, 8 and 17, mean: 10.3). Other patients were assessed for non RRP group (n=19, -9≤SHS≤2: mean: -2.1). Radiographically, there were significant differences between two groups in ΔSHS/y and ΔJEN/y, (P<0.01). In MRI, significant increase of cMRIS oedema at baseline (P<0.05), cMRIS oedema at 1 year (P<0.01) and significant decrease of percentage improvement of cMRIS oedema (P<0.01), cMRIS synovitis (P<0.05), cMRIS erosion + synovitis + oedema (P<0.05) were observed in RRP group compared with non RRP group. These results showed that at baseline, bone marrow oedema in MRI was more predictive than synovitis (P=0.80, NS) or bone erosion (P=0.51, NS) as previously reported (2), and perpetuation of bone marrow edema was important for RRP at 1year. Conclusions: In low field MRI, bone marrow oedema was more associated with occurrence of RRP than synovitis or bone erosion in bio-naïve RA patients during ADA and MTX combination therapy. References: T.Suzuki et al. A new low-field extremity magnetic resonance imaging and proposed compact MRI score: evaluation of anti-tumor necrosis factor biologics on rheumatoid arthritis. Mod.Rheumatol. 2009: 19. 358-365 F.Gandjbakhen et al. Bone marrow oedema predicts structual progression in 1-year follow up of 85 patients with RA in remission or with low disease activity with low-field MRI. Ann.Rheum.Dis.2011:70.2159-2162 Disclosure of Interest: None Declared